"He Sees his Autism as a Strength, Not a Deficit Now": A Repeated Cross-Sectional Study Investigating the Impact of Strengths-Based Programs on Autistic Adolescents. - Lee, Elinda Ai Lim; Scott, Melissa; Black, Melissa H.; D'Arcy, Emily; Tan, Tele; Sheehy, Louise; Bölte, Sven; Girdler, Sonya (Journal of Autism & Developmental Disorders, 2024)
Recent studies have reported that strengths-based programs, leveraging autistic adolescents' abilities and interests, could improve their skills and facilitate social engagement. However, little is known about the long-term impact of strengths-based approaches. This study aimed to explore the long-term outcomes of community strengths-based programs designed to support autistic adolescents in developing interests and skills in Science, Technology, Engineering, Arts, and Mathematics (STEAM) and the factors influencing their participation in these programs. A repeated cross-sectional survey study over three years recruited 52 parents in 2018, 52 parents in 2019, and 38 parents in 2020. Results highlighted the positive impact of these programs on autistic adolescents' health and well-being, social relationships and interactions, self-confidence and self-esteem, sense of belonging, and activities and participation. Five key elements influencing participation included the enthusiasm of the participants, their self-perception, the approach of the programs, the learning environment, and the attitudes of the mentors. This study implies that strengths-based approaches to intervention and support for autistic adolescents in a supported environment are a social model solution that could potentially have positive participant outcomes. Findings from this study could provide a framework underpinning future strengths-based interventions.